Social and Economic Conditions of Student Life in Europe. National Profile of Latvia. Eurostudent IV, 2008-2011 - Dedze, Indra; Strode, Ieva; Rutkovska, Zanda; Kovaleva, Natalja (University of Latvia; Marketing and Public Opinion Research Centre SKDS, 2011)
In Latvia the Eurostudent survey was carried out according to the requirements of the Ministry of Education and Science and was carried out by the Marketing and public opinion research centre SKDS. In Latvia the sample size was 2000 including students from public and private universities in full time study programs. The quota sampling method was applied and only one private higher education institution declined to participate. The survey included 11.9% of respondents from ISCED 5B level and 2.6% from ISCED 6 level students. These groups of respondents were excluded from the international report, thus the sample for the international analysis is 1709 respondents. The sample is representative as it corresponds to the general statistical trends (report of the Higher Education, Ministry of Education and Science, 2009) of the student body in Latvia - 39 % male, 61% female students; 77% - public and 23% private university students.
Keywords: Students; Higher Education; Social Conditions